PERSPECTIVE OF BLOCKCHAIN TECHNOLOGIES APPLICATION IN CORPORATE GOVERNANCE: RECENT TENDENCIES - A. S. Yukhno (Управленческие науки)
The subject of the present paper is the perspective of blockchain technology application based on the experience of the Russian and foreign companies, ﬁnancial institutions, and public authorities. The purpose of the article is to study trends, identify areas of application, and analyze the risks and beneﬁts of blockchain technology application in corporate governance. The author used the methods of generalization, synthesis, comparative analysis of the approaches applied to determine the role played by blockchain in corporate governance, studied appropriate recent scientiﬁc publications, and also conducted the comparative analysis of the corporate governance goals and key characteristics of the above technology. The author has exhaustively analyzed the prospects of blockchain technology implementation in corporate governance taking into account the spread of the COVID-19 pandemic, which forms the novelty of the present paper. The author proposes to follow the below recommendations pertaining to certain issues of implementing blockchain technology into entity’s operations: to include the issue of suitability of blockchain technology integration into the entity’s operations in the meeting of the Board of Directors’ agenda, develop and approve at the Board level in-house documents to regulate the technology application within the entity as well as the strategy of its using to be followed by its integration into the entity’s general business strategy, approve the entity’s risk-appetite to use the technology within the frameworks of the overall entity’s risk management strategy, analyze the impact it may cause on the entity’s activities at the Board level and also ensure improving the employees’ training and competencies with respect to using blockchain technology. The author concludes that nowadays blockchain technology will be most intensively used in areas where it is a more effective alternative to existing systems in their current state. The conclusions and results obtained may be used in the course of developing Russian corporate governance practice as well as in the analytical and practical work performed by the public authorities and the business community.